Multigenerational Influences of the Fut2 Gene on the Dynamics of the Gut Microbiota in Mice - Rausch, Philipp; Künzel, Sven; Suwandi, Abdulhadi; Grassl, Guntram A.; Rosenstiel, Philip; Baines, John F. (Frontiers in Microbiology, 2017)
The FUT2 gene encodes an α-1,2-fucosyltransferase responsible for the expression of ABO histo-blood-group antigens on mucosal surfaces and bodily secretions. Individuals who carry at least one functional allele are known as “secretors”, whereas those homozygous for loss-of- function mutations are known as “nonsecretors”. Nonsecretor individuals are more susceptible to chronic inflammatory disorders such as Crohn Disease, which may be mediated by alterations in the microbiota. Here, we investigated the dynamics of microbial community assembly with respect to genotype using a Fut2-deficient mouse model, taking the genotype of the maternal lineage over two generations into account. We found strong differences in community assembly of microbial communities over time, depending on the Fut2 genotype of the host and that of their progenitors. By applying network analyses, we further identified patterns of specialization and stabilization over time, which are influenced by the host and parental genotype during the process of community development. We also show genotype- and breeding-dependent patterns of community susceptibility to disturbance in a novel in silico approach integrating ecological- and network analysis. Our results indicate that it may be important to investigate the influence of Fut2 genotype in a familial context in order to fully understand its role in the etiology of chronic inflammatory disorders.